Structural analysis of plasmid-mediated verotoxin gene producing non-o157 escherichia coli using molecular dynamic simulations - Khan, M. F. K.; Rashid, S. S.; Ramli, A. N. M.; Kabir, M. N.; Maziz, M. N. H. (Slovak University of Agriculture, 2021)
Plasmid-mediated Non-O157 VTEC is a pathogenic E. coli serotype, are responsible for many life-threatening diseases such as diarrhoea. The thermostable crystal structure has been widely sought after for industry and therapeutic applications through the structural analysis. The National Center for Biotechnology Information (NCBI) Genbank Database has been sourced to obtain plasmid-mediated Verotoxin genes producing non-O157 MN 696158 (Vtx1-1) and MN688720 (Vtx2) sequences. The tertiary structure of MN696158 (Vtx1-1) and MN688720 (Vtx2) was generated by operating MODELLER. The result exposed multiple templates during modelling processes have improved the local stereochemical quality of the produced models. The structural analysis also disclosed the similarities and differences between the models (Vtx1-1 and Vtx2). Furthermore, the thermal stability profile of plasmid-mediated non-O157 VTEC were studied. The molecular dynamics simulations of plasmid-mediated non-O157 VTEC structures (Vtx1-1 and Vtx2) illustrated the interactions between amino acids. On the other hand, Vtx1-1 and Vtx2 showed noticeable differences in their relative conformational flexibility and stability at elevated temperature. However, it is expected that the information of the thermal stable of plasmid-mediated non-O157 VTEC models can be used for potential vaccine candidate through protein engineering in future.